Penerapan Teknik Quilting pada Baju Pesta dengan Sumber Ide Merpati Hijau dan Calathea - Nur Evelynasari; Indarti Indarti (Universitas Negeri Surabaya, 2023)
The green pigeon has beautiful wings dominated by green color. Calathea leaves are oval, striped motif. This study aims to provide a descriptive description of the process of making and finishing the finished party dress by taking the idea of green doves and Calathea leaves, using quilting techniques. This research method uses three stages in the design process (a three stages design process) consisting of problem definition and research, creative exploration and implementation. The initial stage of determining the concept of a women's party dress design that took inspiration from green doves and Calathea leaves focused on feminine and masculine styles. In the second stage, making moodboards and developing ten sketches of women's party dress designs were used as references. The two selected designs were realized through making construction patterns. At the implementation stage, quilting ornaments are applied as the main focus or center of attention in party attire. The process of making quilting uses satin, crinolin, and brocade. The end result of party wear is as expected, by creating dresses that combine feminine and masculine styles. The fashion style looks feminine with a slim bottom skirt and looks masculine at the top using an outer that looks straight and dashing.